“Thinking about My Thinking” The Complex Interplay Between Metacognitive Strategies and Language Skills - Maharani, Gita Nathania; Tresnadewi, Sintha; Karmina, Sari (Pascasarjana UM, 2023)
This systematic literature review employs the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology to comprehensively analyze and synthesize the existing body of research on the complex interplay between metacognitive strategies and English language skills. This review aims to provide a comprehensive overview of the current state of knowledge, identify research gaps, and highlight trends within the field. The synthesized findings highlight the key themes and trends within the complex interplay between metacognitive strategies and English language skills literature. These include the application of metacognitive strategies in the classroom as well as during the learning process, how well they help students learn English skills, and how they affect students' academic achievement and interests. The discussion section critically examines the implications of the identified themes and trends. It highlights the advancements made in understanding the complex interplay between metacognitive strategies and English language skills, areas where further research is needed, and potential practical applications of the research findings.